Pembaharuan Pengaturan Tindak Pidana Perzinahan dalam Undang-Undang Nomor 1 Tahun 2023 tentang KUHP dan Implikasinya terhadap Perlindungan Keluarga serta Hak Privasi - devita devi (Jurnal Hukum Lex Generalis, 2026)
This study analyzes the reform of adultery offense regulation under Article 411 of Law Number 1 of 2023 on the Criminal Code. It uses normative juridical research with a statutory approach. The findings show that Article 411 expands the subject of adultery through the phrase “every person”, but limits prosecution through a complaint offense by a spouse, parent, or child. This provision strengthens family protection, yet requires technical guidelines to prevent privacy violations and misuse in law enforcement.